The role of learning in nurturing knowledge, attitude and practice of toilet hygiene among youth in Malaysians university - Ahmad, Zeti Azreen; Abdul Manan, Kamaruzzaman; Ahmad Tajuddin, Siti Nor Amalina; Ali, Roslan (AHAS KIRKHS IIUM, 2021)
In Malaysia, the cleanliness of public toilets continues to be a challenge. A dirty toilet could become a site that spreads diseases and hurts the image of the country as a whole. Even though campaigns promoting good toilet hygiene practices have been ongoing since 1997, not much has been achieved from these campaigns. A good toilet hygiene practice requires knowledge and the right attitude among users. Therefore, early education is required to shape the public’s perception and influence their practice of toilet hygiene. Hence, this study selected the Knowledge Attitude and Practice (KAP) theory to measure the factors influencing university students’ toilet hygiene practices. Moreover, the learning factor was added to the theory to see how the teaching and learning process affects the knowledge and attitude of youth. This study used the partial least squares (PLS) method and structural equation modelling (SEM) software to examine the selected factors. The results show that respondents level knowledge (87%), attitude (88%), practice (81%) and learning (79%) on toilet hygiene are high. Moreover, learning, knowledge, and attitude have a significant influence on the practice of toilet hygiene. This study has extended the KAP theory by adding learning as a factor that influences youth’s knowledge and positive attitude towards toilet hygiene. The findings are useful for policymakers, higher education institutions, and public relations (PR) practitioners in their effort to improve campaign strategies to generate attitudinal and behavioural change towards hygiene and cleanliness issues. Limitations and suggestions for future research are also included in this paper